A review of nanostructured thin films for gas sensing and corrosion protection - Ho, Soon Min; S.A, Vanalakar; Ahmed, Galal; Vidya, Nand Singh (2018)
Thin film technology is getting huge attention across the world due to its wide applications. Deposition of thin films involves creation, transportation and condensation of target materials with thickness varying from few nanometers to several microns onto the substrate. This review will highlight thin film depositing techniques which consist of non-vacuum and vacuum based deposition method. Besides this, thin films and their applications in gas sensing and corrosion protection have also been discussed